A critical analysis of interventionist theatre strategies: a case study of Hisia, Lumumba and Mlimani Performers Theatre Groups in Dar es Salaam - Mtiro, Chahya James (My University, 2010)
ABSTRACT This study: “A Critical Analysis of Interventionist Theatre Strategies: A Case Study of Hisia, Lumumba and Mlimani Performers Theatre Groups in Dar es Salaam” attempts to explore how interventionist strategies are framed to make them communicate specific messages to specific target communities. Through this exploration we expect to map out what might be considered as appropriate strategies that would be deployed in communicating HIV/Aids issues and messages more effectively. This study is motivated by the realisation that there has been inadequate focus by previous studies on youth intervention theatre strategies in Dar es Salaam particularly and Tanzania in general. Our study employed qualitative research in order to acquire in-depth understanding of how the three groups in Dar es Salaam deploy techniques of applied theatre in their HIV/Aids intervention initiatives. The methods utilised included observation and structured interviews. The study was theoretically guided by the ideas of Augusto Boal and Paulo Freire. Freire demonstrates how the marginalised populations regain their lost voices through dialogue and problem-posing education, a situation whereby the roles of the educators and educatees are flexible and interchangeable. The study also draws heavily from Boal, especially his argument that lack of power creates fears in peoples’ heads, what he describes as cops in our heads. Boal believes that all the cops in our heads have identities and headquarters in the external world that need to be located. This is one way in which oppressed people can confront their internalised forms of oppression. If we are to draw an analogy from Boal, the HIV/Aids conditions that disempower infected people can be interpreted as an oppressive situation. The findings of this study reveal weaknesses in the methods which are deployed by the applied theatre practitioners in HIV/Aids intervention initiatives. This study therefore suggests a rethinking in the way that intervention theatre practices are framed to make them become more effective tools of communicating issues and messages related to HIV and AIDS.